Identifying and Understanding Barriers and Facilitators to Medication Adherence Among Marshallese Adults in Arkansas. (October 2018) - McElfish, Pearl A.; Balli, Michelle L.; Hudson, Jonell S.; Long, Christopher R.; Hudson, Teresa; Wilmoth, Ralph; Rowland, Brett; Warmack, T. Scott; Purvis, Rachel S.; Schulz, Thomas; Riklon, Sheldon; Holland, Angel; et al.
Background: Significant health disparities are present in Marshallese adults residing in the United States, most notably a high incidence of type 2 diabetes and other chronic conditions. There is limited research on medication adherence in the Marshallese population.Objective: This study explored perceptions of and experiences with medication adherence among Marshallese adults residing in Arkansas, with the aim of identifying and better understanding barriers and facilitators to medication adherence.Methods: Eligible participants were Marshallese adults taking at least one medication for a chronic health condition. Each participant completed a brief survey and semistructured interview conducted in Marshallese by a bilingual Marshallese staff member. Interviews were recorded, transcribed, and translated from Marshallese to English. Qualitative data were coded for a priori and emergent themes.Results: A total of 40 participants were included in the study. The most common contributing factor for nonadherence was forgetting to take medication (82%). A majority of participants (70%) reported difficulty paying for medicine, 45% reported at least one form of cost-related nonadherence, and 40% engaged in more than one cost-related nonadherence practice. Family support and medication pill boxes were identified as facilitators for medication adherence. The majority of the participants (76.9%) stated that they understood the role of a pharmacist. Participants consistently desired more education on their medications from pharmacy providers.Conclusion: This is the first study to explore barriers and facilitators to medication adherence among Marshallese patients. The findings can be used to develop methods to improve medication adherence among Marshallese.